Clinical value of DNA content assessment in endometrial cancer. Issue 3 (14th February 2014) - Mauland, Karen Klepsland; Wik, Elisabeth; Salvesen, Helga Birgitte
<x xml:space="preserve">Abstract</x> Endometrial carcinoma (EC) is the most common gynecologic cancer in industrialized countries. Traditional prognostic markers include FIGO stage, histologic subtype, and histologic grade. DNA ploidy was introduced as a prognostic marker 30 years ago, and the majority of published literature demonstrates significant associations between tumor aneuploidy and poorer prognosis in EC. However, ploidy analysis is not routinely implemented in the clinic. We reviewed the literature on clinical value of ploidy measured by DNA content as a prognostic marker, and its potential role as a predictive marker in EC. PubMed was searched for papers evaluating the prognostic or predictive role of ploidy in EC. Search criteria were "DNA ploidy prognosis/predictive value endometrial cancer/carcinoma". Only articles written in English, published year 2000 or later were included. The majority of the studies demonstrated highly significant correlation between DNA index (DI) and survival, in univariate analysis including stages I–IV, and in subgroup analysis of stage I and stage I–II EC. Several studies also showed significant association between DI and survival in multivariate analysis. Few studies have evaluated DI as a prognostic marker in a prospective setting. No studies evaluating DI as a predictive marker in EC were identified. In other cancer types, ploidy has been linked to prediction of response to hormonal therapy and chemotherapy. Ploidy assessment in EC by DI is a strong prognostic marker. Still, its clinical applicability needs validation in a routine diagnostic, prospective setting with sufficient number of patients, characterized by state of the art histopathological evaluation and surgical staging. © 2014 International Clinical Cytometry Society